Fruit set and the diurnal pollinators of the invasive Lantana camara and the endemic Lantana peduncularis in the Galapagos Islands. Issue 3 (5th August 2014) - Carrión‐Tacuri, Jorge; Berjano, Regina; Guerrero, Giovanny; Figueroa, Enrique; Tye, Alan; Castillo, Jesus M.
<x xml:space="preserve">Abstract</x> Fruit set is highly relevant to a plant's reproductive success. Fruit set can vary due to predation on flowers, pollinator services and/or resource availability. Reproductive success, measured as the fruit set of the invasive Lantana camara and the endemic Lantana peduncularis in the cool–dry season and the warm–wet season of the Galapagos Islands, was studied. Also, autonomous self‐pollination ability and seed viability were probed for both species. Furthermore, flower visitors and their activity were registered for both species during the warm–wet season. Lantana peduncularis produced fewer flowers per inflorescence, but had a higher fruit set in the cool–dry season, compared to the warm–wet season. In contrast, the fruit set in L. camara did not change seasonally. The fruit set in L. camara was higher than in L. peduncularis in the warm–wet season. Moreover, ∼18% of the bagged flowers of the invasive Lantana produced fruits by autonomous self‐pollination, while for the endemic Lantana, the rate of autonomous self‐pollination was very low. More than 80% of the fruits for both species had at least one viable seed per fruit. The number of pollinators and their frequency, inflorescence‐ and flower‐visiting rates and the duration of the visit per flower were higher in the invasive Lantana than in the endemic one. The endemic Lepidoptera Urbanus galapagensis (the main pollinator of both Lantana species) and the introduced Hymenia perspectalis were observed pollinating both Lantana species. These results indicate that the alien L. camara is more attractive to pollinators and it has reproductive advantages regarding fruit set in comparison with L. peduncularis, factors that contribute to the colonization pattern of this invasive species.